The Subacute Toxicity of Perfluorooctane Sulfonate and/or Perfluorooctanoic Acid and Legacy Aqueous Film‐Forming Foams to Japanese Quail (Coturnix japonica) Chicks. (31st March 2020) - Bursian, Steven J.; Link, Jane E.; McCarty, Michael; Simcik, Matt F.
Abstract: As part of an effort to develop avian ecotoxicity information for poly‐ and perfluoroalkyl substances (PFAS) including perfluorooctane sulfonate (PFOS) and perfluorooctanoic acid (PFOA) associated with aqueous film‐forming foam (AFFF) used by the Department of Defense, the subacute toxicity of PFOS, PFOA, PFOS + PFOA, 3M AFFF, and Ansul AFFF to Japanese quail ( Coturnix japonica ) chicks was determined. Ten‐day‐old Japanese quail were administered treated feed for 5 d and then fed untreated feed for 18 d. Analyzed concentrations of PFOS, PFOA, and PFOS + PFOA ranged from 62 to 1955, 162 to 1208, and 43 + 45 to 296 + 292 mg kg feed –1 . Analyzed concentrations of PFOS in feed containing the 3M AFFF ranged from 73 to 1399 mg kg feed –1, and formulated concentrations of 6:2 fluorotelomer thioamido sulfonate in feed containing the Ansul AFFF ranged from 9 to 1118 mg kg feed –1 . Average daily doses resulting in 50% mortality at day 5 were 38 (34–43), 68 (63–74), 55 (51–59), and 130 (103–164) mg PFOS, PFOA, PFOS + PFOA, and PFOS in 3M AFFF kg body weight –1 d –1 . Ansul AFFF did not result in any mortalities. Dietary concentrations resulting in 50% mortality at day 5 were 351 (275–450), 496 (427–575), 398 (339–468), and 467 (390–559) mg PFOS, PFOA, PFOS + PFOA, and PFOS in 3M AFFF kg feed –1 . Environ Toxicol Chem 2021;40:695–710. © 2020 SETAC